Composition and antifungal activity against candida albicans, candida parapsilosis, candida krusei and cryptococcus neoformans of essential oils from leaves of piper and peperomia species - Morandim-Giannetti, Andreia de Araujo [UNESP]; Pin, Aline Ringis; Pietro, Natalia Ama Santo; de Oliveira, Haroldo Cesar [UNESP]; Mendes-Giannini, Maria Jose Soares [UNESP]; Alecio, Alberto Camilo [UNESP]; Kato, Massuo Jorge; de Oliveira, Jose Eduardo [UNESP]; Furlan, Maysa [UNESP] (My University, 2010)
This study was addressed to investigate the composition and antifungal activity of essential oils from leaves of Piperaceae species (Piper aduncum, Piper amalago, Piper cernuum, Piper diospyrifolium, Piper crassinervium, Piper gaudichaudianum, Piper solmsianum, Piper regnellii, Piper tuberculatum, Piper umbelata and Peperomia obtusifolia) against Candida albicans, C. parapsilosis, C. krusei and Cryptococcus neoformans. The essential oils from P. aduncum, P. gaudichaudianum and P. solmsianum showed the highest antifungal activity against Cryptococcus neoformans with the MIC of 62.5, 62.5 and 3.9 mg.mL-1, respectively. The oil from P. gaudichaudianum showed activity against C. krusei with MIC of 31.25 mg.mL-1. © 2010 Academic Journals.
Keywords: Antifungal activity; Essential oil composition; GC-MS; Peperomia; Piper; Piperaceae